Animated videos in assessment: comparing validity evidence from and test-takers' reactions to an animated and a text-based situational judgment test. Issue 2 (15th June 2021) - Karakolidis, Anastasios; O'Leary, Michael; Scully, Darina
Abstract: The linguistic complexity of many text-based tests can be a source of construct-irrelevant variance, as test-takers' performance may be affected by factors that are beyond the focus of the assessment itself, such as reading comprehension skills. This experimental study examined the extent to which the use of animated videos, as opposed to written text, could (i) reduce construct-irrelevant variance attributed to language and reading skills and (ii) impact test-takers' reactions to a situational judgment test. The results indicated that the variance attributed to construct-irrelevant factors was lower by 9.5% in the animated version of the test. In addition, those who took the animated test perceived it to be more valid, fair, and enjoyable, than those who took the text-based test. They also rated the language used as less difficult to understand. The implications of these findings are discussed.